A comparative profile of urinary scent signals of two endangered Japanese populations of leopard cat - Ichizawa, Shota; Uenoyama, Reiko; Nakanishi, Nozomi; Endo, Yasuyuki; Suka, Ayaka; Izawa, Masako; Miyazaki, Masao (Frontiers in Ecology and Evolution, 2023)
Two subspecies of mainland leopard cats (Prionailurus bengalensis), Iriomote cats (Prionailurus bengalensis iriomotensis) and Tsushima leopard cats (Prionailurus bengalensis euptilurus), are small, endangered felids that are endemic to the Japanese islands, Iriomote-jima and Tsushima, respectively. Both subspecies have an estimated population size of only about 100 individuals each. Therefore, it is crucial to expand our understanding of these subspecies to successfully conserve them. While their morphology, anatomy, ecology, pathology, and genetics are well studied, little is known about their physiology regulated in subspecies-specific manners. This study characterized their urinary volatile and nonvolatile organic compounds, with which individuals express their physiological status and territorial ownership. We found significantly higher levels of 3-mercapto-3-methyl-1-butanol and its structural analogs, which are scent signals of domestic cats, in the urinary headspace of Iriomote cats than in that of Tsushima leopard cats. There were no differences in the urinary levels of felinine, an amino acid that acts as a precursor of 3-mercapto-3-methyl-1-butanol, suggesting the variation of catalytic activities for decomposing felinine to 3-mercapto-3-methyl-1-butanol between subspecies. Both subspecies exhibited physiological proteinuria due to the secretion of carboxylesterase 5A, also known as cauxin, for the production of felinine. In conclusion, while the two endangered Japanese subspecies of mainland leopard cats share similar genetic backgrounds, urinary contents of metabolites vary between the subspecies. We suggest that after the separation into two subspecies, the regulation of the metabolic pathway for 3-mercapto-3-methyl-1-butanol production likely evolved differently in each subspecies in response to their specific environments.